Acute colonic pseudo‐obstruction leading to perforation: a case‐control study investigating associations to tapentadol. (13th May 2020) - Scott, Matthew; Konstantatos, Alex H.; Bui, Thuy; Carne, Peter; O'Donohoe, Rory; Dearaugo, Stephanie; Donovan, Sarah
Abstract: Background: Acute colonic pseudo‐obstruction (ACPO) is an uncommon syndrome where the large bowel dilates in the absence of mechanical obstruction and may progress to perforation. A recent increase in the incidence of ACPO complicated by colonic perforation had been noted at the Alfred Hospital, coinciding with the introduction of the analgesic tapentadol. This led to an investigation of potential associations between complicated ACPO and tapentadol, together with other identifiable factors. Methods: This was a retrospective case‐control study. Eight cases were identified and confirmed radiologically. Four matched controls were identified for each case based on age, sex and comparable diagnosis at the time of presentation. Results: Thirty‐five male and five female patients of similar age and comorbid disease were reviewed. Tapentadol use (p = 0.42) and duration (p = 0.81) and mean tapentadol dose (p = 0.07) did not differ between groups. Other associations included alcohol use of greater than three standard drinks per day (p = 0.031) and ondansetron use (p = 0.039) among cases. Mean (± SD) duration of opioid use was significantly longer in the cases than controls (7.6 ± 1.6 vs 5.0 ± 3.1 days respectively; p = 0.023; odds ratio 2.57, 95% confidence interval 1.1–5.8). Mean opioid dose (p = 0.68) did not differ between groups. Conclusion: Pseudo‐obstruction causing colonic perforation was associated with alcohol use of greater than three standard drinks per day, longer in‐hospital opioid use and ondansetron use, but not with the use, duration or mean dose of tapentadol. Data should be combined with data from other sites to strengthen associations.